Prognostic Significance and Advantage of Echocardiography in The Diagnosis of Ischemic Heart Disease (Eurasian Medical Research Periodical, 2023)
The control group consisted of 20 conditionally healthy patients aged 60 years (49.1 ± 2.98) without clinical manifestations of coronary artery disease and the absence of its main risk factors. Depending on the clinic, the results of the study, the patients were divided into 2 groups. Group I patients consisted of 20 conditionally healthy men aged 37 to 61 years (49.2 ± 2.87) with two risk factors for IHD. Group II included 20 men aged 39 to 64 years (49.5 ± 3.01) with typical bouts of exertional angina. All the examined patients underwent tissue stress-DehoKG technique with physical activity. Physical activity according to the method was used as a stress agent.